The role of Ca-bridged organic matter in an alkaline soil, as revealed by multimodal chemical imaging - Tamas Varga; Ravi K. Kukkadapu; Libor Kovarik; Alice C. Dohnalkova; Qian Zhao; Mark H. Engelhard; Swarup China; Nurun Nahar Lata; Anil K. Battu; Rosalie K. Chu; Matthew A. Marcus; Thomas W. Wietsma; et al. (Geoderma)
Mineral–organic matter (OM) studies have predominantly focused on acidic soils that are abundant in iron (Fe) oxides and aluminum (Al) oxides. We have probed mineral–OM interactions in an alkaline or calcareous soil of the Aridisols class. Unlike the role of Fe and Al, the role of Ca-minerals (particularly calcite), which are ubiquitous in alkaline soils, in OM sequestration is not well understood. Multiple recent model studies with aqueous Ca2+ or synthetic calcite and a suite of OM compounds have shown Ca-OM assemblages to be spatially correlated with calcite at the microscale. To study the chemical state of both Ca and Fe and their competing role in soil organic matter (SOM) stabilization, we performed laboratory characterization using x-ray diffraction, Mössbauer spectroscopy, x-ray photoelectron spectroscopy, scanning electron microscopy, and scanning transmission electron microscopy, alongside synchrotron-based microscale chemical imaging using scanning transmission x-ray microscopy combined with near-edge x-ray absorption fine structure. Ca mineral–organic associations were found to be ubiquitous in this system and are likely critical for understanding SOM stabilization/degradation in alkaline soils. From our findings on mineralogy, speciation, and the nature of Ca-OM bridging, we identified differences in C and Ca chemistry based on the relative location of OM to Ca minerals. The OM near the calcite crystal was enriched in lipid and protein moieties, Ca-OM next to Fe minerals displayed a strong contribution from aromatic compounds, while on the surface of microbes, the carbonate was believed to be of microbial in origin, as also suggested by preliminary works reporting on the formation of amorphous calcite or nano-calcite. In Ca-OM admixed with carbonate, it was difficult to distinguish Ca-associated OM from amorphous calcite or nano-calcite.